ACTIVE TRANSPORTATION ON FORT RILEY ARMY INSTALLATION: A FIELD EXPERIENCE REPORT - Lightner, Joseph S. (My University, 2013)
This report was focused on my field experience at the Department of Public Health at Fort Riley Army Installation. The purpose of this report was two-fold. First, I have outlined and described my experiences with various groups within the Department of Public Health. Second, I aimed to evaluate policies and programs focused on promoting environmental change for walking and biking and gave direction to the Army Corp of Engineers on best practices for walking and biking for transportation. The objectives were to identify key agencies responsible for bike and pedestrian infrastructure, understand how those agencies could work together to improve the built environment for walking and biking and develop intervention strategies to improve walking and biking on Fort Riley.
Keywords: Fort Riley Kansas; Public Health; Built environment; Public Health (0573)